2018
DOI: 10.1038/s41598-018-22687-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic therapy enhanced by the peptide aurein 1.2

Abstract: In the past few years, the World Health Organization has been warning that the post-antibiotic era is an increasingly real threat. The rising and disseminated resistance to antibiotics made mandatory the search for new drugs and/or alternative therapies that are able to eliminate resistant microorganisms and impair the development of new forms of resistance. In this context, antimicrobial photodynamic therapy (aPDT) and helical cationic antimicrobial peptides (AMP) are highlighted for the treatment of localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 58 publications
3
55
0
Order By: Relevance
“…In the case of another photosensitizer curcumin, the synergistic effect was not observed at all. This proves that the enhanced action of aPDI and AMP was PS-dependent ( de Freitas et al, 2018 ). In our studies, RB proved to be very good PS for combined aPDI and AMP action, whereas it is commonly known that RB itself is not effective against Gram-negative species ( Bezman et al, 1978 ; Schafer et al, 2000 ; Demidova and Hamblin, 2005 ; Wen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In the case of another photosensitizer curcumin, the synergistic effect was not observed at all. This proves that the enhanced action of aPDI and AMP was PS-dependent ( de Freitas et al, 2018 ). In our studies, RB proved to be very good PS for combined aPDI and AMP action, whereas it is commonly known that RB itself is not effective against Gram-negative species ( Bezman et al, 1978 ; Schafer et al, 2000 ; Demidova and Hamblin, 2005 ; Wen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 57%
“…This further means that a PS does not have to be accumulated inside the cells to perform an efficient photodynamic action ( Preuss et al, 2013 ). For example, chlorin-e6 uptake was significantly decreased in the presence of AMP, however, the synergistic action of aPDI and AMP was still observed ( de Freitas et al, 2018 ). Such a characteristic of aPDI is an advantage as it means that bactericidal action can be started from the outside of the cell rather than from the inside where DNA could be affected and potentially mutagenized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was possible to perceive that MB accumulated inside prokaryote cells, while chlorin e 6 attached to the outside of bacterial cells. The studies revealed not only distinct mechanisms of action, but also evidenced the multiple-target nature of the photodynamic effect [100].…”
Section: Oligopeptidesmentioning
confidence: 95%
“…Positively charged molecules, such as the polymixin B nonapeptide, have been used to functionalize PSs for PACT applications by improving their internalization by different strains of Gram-negative bacteria. 78 Chlorin e 6 (56), a chlorophyll-derived tetrapyrrole, combined with the cationic polymer polyethylenimine (PEI) also showed PACT efficiency against some strains of Gram-negative bacteria. 79 Indeed, PSs possessing a positively charged molecular structure, such as tetracationic porphyrins, phthalocyanines and dyes such as toluidine blue O (31) or methylene blue (30), are the most suited to eliminate tough Gram-negative species of bacteria.…”
Section: Cancer Therapymentioning
confidence: 99%